Development of comic with discovery learning model as a media to increase students’ literacy in primary school - Nurjannah, Isna Fitri; Wahyudi, Wahyudi; Setiawan, Yohana (Jurnal Pendidikan dan Pengajaran, 2019)
The purpose of this study was to develop and test the validity, practicality, and effectiveness of comic media based on Discovery Learning in thematic learning in primary school. This research method is R & D and uses the ADDIE design which has 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. The validity of the module is analyzed using the expert test, the practicality of the product is seen from the student response questionnaire towards the media while the effectiveness of the module is analyzed using the results of analysis in accordance with the three aspects of literacy namely the process of understanding, reading goals, and reading behavior from the theme and comic books and paired-samples test t-test. The results of research on comic-based learning media with the Discovery Learning approach to improve the literacy of grade III elementary school students. Comics proved valid based on expert tests conducted. Evaluation of the media aspect validator obtained a score of 69 with a percentage of 92%. The material aspect validator got a score of 43 with a percentage of 86% and the learning aspect Validator got a score of 41 with a percentage of 82%. the comics proved to be practical based on the student questionnaire responses to the media, the researchers responded to give questionnaires to 35 grade III students obtained a percentage of 91%. Comics proved effective based on analysis of analysis results in accordance with the assessment of the three aspects of literacy, namely the process of understanding, reading goals, and reading attitudes from theme and comic books with an increase in reading theme books that obtained percentages from 80% to 92% after reading comics. an increase of 12%, and the results of the pretest and posttest at the significance level of 0,000. The average pretest was 62.89 while the posttest average was 86.34. Effectiveness can be seen from the increase in the number of students who achieve grades above the KKM. As many as 100% of students were declared complete at posttest while at pretest the number of students completed was 8.57%.